2011
DOI: 10.1111/j.1460-9592.2011.03578.x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal foreign bodies in children: considerations for the anesthesiologist

Abstract: The combination of a curious young child exploring his/her nasal cavities, with the abundance of small inert and natural objects in our society, culminates in a significant number of nasal foreign bodies (NFBs). Usually NFBs are benign entities, yielding relatively simple resolutions and mild morbidities. However, their presence can lead to much more serious consequences if they are inserted unwitnessed, grow asymptomatically for several months or years, and significantly affect surrounding tissues. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Although the characteristics of foreign bodies are not very important, children may nudge every foreign body, mainly pieces of bread, cotton, paper, erasers, corns, plant beads, plastic substances, and living bodies into their nose [4][5][6][7][8] .Most nasal foreign body cases are seen in children aged between 1 and 3 years. Although various information has been reported about the dominant sex, it is more frequently reported among male children [7][8][9][10] . Çetinkaya et al [11] performed a study with 1875 cases and indicated that 52.9% of the cases who inserted foreign bodies through their nostrils were male.…”
mentioning
confidence: 99%
“…Although the characteristics of foreign bodies are not very important, children may nudge every foreign body, mainly pieces of bread, cotton, paper, erasers, corns, plant beads, plastic substances, and living bodies into their nose [4][5][6][7][8] .Most nasal foreign body cases are seen in children aged between 1 and 3 years. Although various information has been reported about the dominant sex, it is more frequently reported among male children [7][8][9][10] . Çetinkaya et al [11] performed a study with 1875 cases and indicated that 52.9% of the cases who inserted foreign bodies through their nostrils were male.…”
mentioning
confidence: 99%
“…Injuries and complications due to the insertion of FB in the nasal fossa are more common than in the ear because the FB might grow asymptomatically for several months or years and affect surrounding tissues. Moreover, the nasal FB is likely to move posteriorly up to the upper airways with consequent severe circumstances [ 32 ]. The development of complications is statistically related to the time elapsed between the FB insertion and the diagnosis, the age of the patient and the experience of the operator [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It occurs in individuals who swim in streams or drink the infested water (1). Possible attachment areas are the nasal cavity, the oropharynx and hypopharynx, the larynx, the trachea, and the esophagus (3,4).…”
mentioning
confidence: 99%
“…Signs of blood loss and obstruction can be seen, such as epi-staxis, hemoptysis, melena, severe anemia, dysphorea, and dyspnea depending on the site of attachment. Symptoms can progress over time, because the leech will increase its size with the time period of its feeding (2)(3)(4). A living leech in the respiratory tract is a rare but an emergency situation.…”
mentioning
confidence: 99%
See 1 more Smart Citation